2011
DOI: 10.1097/mjt.0b013e3181c9dac6
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sclerosing Cholangitis Associated with Elevated ImmunoglobulinG4: Clinical Characteristics and Response to Therapy

Abstract: Steroid responsive biliary strictures in patients fulfilling criteria for primary sclerosing cholangitis (PSC) have been reported. The clinical course and response to therapy in patients with PSC with elevated immunoglobulin G4 (IgG4) levels has not been investigated previously. Patients with PSC were screened for IgG4-related biliary disease during 2006 to 2008 and data were collected prospectively. A total of 33 out of 285 (12%) patients with PSC (18 males) had elevated IgG4 (>140mg/dL) with a median age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 21 publications
0
67
0
3
Order By: Relevance
“…Importantly, slight elevations (up to 5 g/L) of serum IgG4 of uncertain relevance occur also among PSC patients not fulfilling criteria for IgG4 associated cholangitis. Among these patients, a more aggressive disease course is often seen [75], but the pathogenetic significance of the detected serum IgG4 elevation and management of these patients have not been defined.…”
Section: Igg4 and Sclerosing Cholangitismentioning
confidence: 99%
“…Importantly, slight elevations (up to 5 g/L) of serum IgG4 of uncertain relevance occur also among PSC patients not fulfilling criteria for IgG4 associated cholangitis. Among these patients, a more aggressive disease course is often seen [75], but the pathogenetic significance of the detected serum IgG4 elevation and management of these patients have not been defined.…”
Section: Igg4 and Sclerosing Cholangitismentioning
confidence: 99%
“…The positive predictive value in relation to IAC in patients who had serum IgG-4 levels between 1 and 2 times higher than the normal levels was 28%. A study by Björnsson et al (20) conducted on 285 patients with PSC found that 12% of patients had higher than normal serum IgG-4 levels and of these, 4 patients (17%) had pancreatic involvement. The use of serum IgG-4 in the diagnosis of IAC from PSC is helpful, but should not be used as the sole factor for the diagnosis of IAC (1,11).…”
Section: Studies Conducted By Boonstra Et Al (19) On Psc Patientsmentioning
confidence: 99%
“…IgG4 associated sclerosing cholangitis (IgG4-SC) -as a variant of PSC -had been correctly reclassified as IgG4-RD-SC) [4]. Being characterized by a favorable response to glucocorticoids and immunosuppressive agents makes the distinction between IgG4-SC and PBC mandatory [5]. The diagnostic value of IgG4 serum levels is questioned as about 40% of IgG4-RD patients have normal serum levels [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Being characterized by a favorable response to glucocorticoids and immunosuppressive agents makes the distinction between IgG4-SC and PBC mandatory [5]. The diagnostic value of IgG4 serum levels is questioned as about 40% of IgG4-RD patients have normal serum levels [4,5]. Interplay between IgG4 positive tissue immunostaining, along with both clinical and cholangiographic features of cholangiopathy, is required for proper diagnosis [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation